Minimum Wage Policy and Country's Technical Efficiency - Karim, Mohd Zaini Abd; Chan, Sok-Gee; Hassan, Sallahuddin (International Journal of Economics and Financial Issues, 2016)
Recently, the government has decided that Malaysia would introduce a minimum wage policy. However, some quarters argued against the idea of a nationwide minimum wage asserting that it will lead to an increase in the cost of doing business and thus will hurt Malaysian competitiveness. Although standard economic theory unambiguously implies that wage floors have a negative impact on employment, the existing empirical literature is not so clear. Some studies have found the expected negative impact on employment, yet others have found no impact or, in occasional cases, a positive effect of minimum wages on jobs. It is also argued that, a minimum wage law, if pegged above the market wage, could leads to a general misallocation of resources and loss of efficiency in the overall economy. However, there is no study linking minimum wage on a country's efficiency. Hence, the objective of this study is to analyse the effect of minimum wage policy on a country's technical efficiency. To achieve the objective, in the first stage, we estimate technical efficiency for all the sample countries by using the non-parametric method. In the second stage, after having estimated the efficiency scores, we analysed the effect of minimum wage on efficiency by estimating a Tobit regression fixed-effect model where the efficiency scores is included as the dependent variable. Results of the study show that there is no difference in technical efficiency between countries with and without minimum wage policy. Hence, minimum wage policy is not harmful to an economy's efficiency. Furthermore, looking at the countries with minimum wage policy, the amount of minimum wage up to a certain level has a positive effect on economic efficiency. The results suggest that minimum wage helps in increasing a country's efficiency provided that the rate does not exceed the optimal level. Keywords: Minimum wage, efficiency, non-parametric, Tobit, competitiveness JEL Classification: J30